2020
DOI: 10.3390/su12083423
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Ammonium from Swine Wastewater Using Synthesized Zeolite from Fly Ash

Abstract: Synthetic zeolites with pretreated fly ash as a raw material were used to remove ammonium from wastewater using a hydrothermal method in this study. Two pretreatment methods of fly ash were used to compare the ammonium removal of zeolites: water-washing and pickling. In addition, the effects of several factors including the time, temperature, pH, adsorbent dosage, coexisting ions and initial concentration were investigated to gain insight into the adsorption rate, behavior and mechanism of synthetic zeolites f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 49 publications
0
19
2
1
Order By: Relevance
“…erefore, the rapid utilization of the most easily available adsorption sites of EMRZ made high-speed diffusion and realization of rapid equilibrium possible. Namely, the quick utilization of the most readily available adsorbing sites of the EMRZ leads to fast diffusion and attainment of rapid equilibrium [25][26][27]. Based on these results and analysis, the contact time of 100 min was used in the following experiment.…”
Section: Resultsmentioning
confidence: 99%
“…erefore, the rapid utilization of the most easily available adsorption sites of EMRZ made high-speed diffusion and realization of rapid equilibrium possible. Namely, the quick utilization of the most readily available adsorbing sites of the EMRZ leads to fast diffusion and attainment of rapid equilibrium [25][26][27]. Based on these results and analysis, the contact time of 100 min was used in the following experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Different type of zeolites affect adsorption capacity differently. For example, zeolite prepared from raw fly which has a slow adsorption capacity for NH4 + , and its application is in fields with high concentration wastewater is limited [40]. In this present study, the different amounts of CZ used for N, P, and K adsorption affected the N, P, and K in equilibrium solutions and this observation is consistent with the findings of Tang et al [40] who also reported that adsorption equilibrium between adsorbent and adsorbate is controlled by the adsorbent dosage.…”
Section: Nitrogen Phosphorus and Potassium In Equilibrium Solutionmentioning
confidence: 99%
“…The similarity of composition between fly ash and zeolite, which is mainly SiO2-Al2O3-CaO-Fe2O3, makes it is possible to convert that ash to zeolite. Distinctive approaches have been utilized, the hydrothermal method by using an alkaline medium and with fusion pre-treatment at high temperatures for zeolite synthesis [18][19][20][21][22][23][24][25]. The distinctions concern solution/fly ash activation ratio, sort of solution, type and molarity of the alkaline agents, temperature, reaction time, pressure, and crystallization time.…”
Section: Introductionmentioning
confidence: 99%